Desafios para a formação educacional dos surdos no Brasil : uma análise crítica e discursiva das representações dos atores sociais sobre a temática do ENEM 2017 - Lima, Fabíola dos Santos (2018)
Taking into account the social inequality that strikes the deaf community, this research aims to analyze critically the discursive manifestations on the Facebook pages of INEP, from MEC, and from the Folha de S. Paulo about the essay’s theme of ENEM 2017, namely “Challenges for the education of deaf individual in Brazil”. As the starting point, it considers the discursive representations of the social actors and the evaluative impressions of internet users about the theme. In this regard, deaf studies, Critical Discourse Analyses (ACD) (FAIRCLOUGH, 2001), dialoguing with the contributions of Van Leeuwen (1998) about the Representation of the Social Actors and with the Thompson’s studies (2002) regarding the modes of operation of ideology were primordial. To handle the linguistic analysis, considering that, according to the ACD, the analysis must be textually orientated, it was utilized the Almeida studies (2010) about Appraisal, specifically the Subsystem of Attitude, because the evaluations of the internet users about the essay’s theme of ENEM 2017 were the target of analysis. The research follows the qualitative-interpretative methodology, and the corpus is composed by 60 commentaries of Facebook derived from the announcement of the essay’s theme of ENEM, in November 5th, 2017. The commentaries were singled out from the Facebook pages of MEC (Ministry of Education and Culture), body responsible for the National Education Policy, from INEP (National Institute Anísio Teixeira), which has the role of organizing and elaborating the National Examination of High School Students (ENEM), and the page of Folha de São Paulo, one of the biggest journalist medias of the country. The research brings to the light how internet users of those pages position themselves in the face of the theme that brings as protagonist the deaf community. We intend to elucidate if, in the discursive practices of the internet users, the social inclusion is manifested and how the ideological social relations occur. To sum up, it was possible to realize that the ideologies orientates the internet users to positive or negative evaluations and those orientations are attached to the reality that surrounds the internet user.